Assessment of Potential Toxic Effects of Fungicide Fludioxonil on Human Cells and Aquatic Microorganisms - Maria Antonopoulou; Anna Tzamaria; Sotiris Papas; Ioanna Efthimiou; Dimitris Vlastos (Toxics)
Fludioxonil is a widely used fungicide that is frequently used to combat fungal plant diseases. Consequently, excessive concentrations of fludioxonil may enter and accumulate over time in aquatic systems, harming (micro) organisms in several ways. Thus, it is of great importance to evaluate the potential toxic effects of fludioxonil using bioassays. In the present study, various in vitro assays were used to assess the possible effects of fludioxonil in human cells and aquatic microorganisms. For the investigation of the toxic effects of fludioxonil on freshwater microalgae, Scenedesmus rubescens and Dunaliella tertiolecta were exposed to various environmentally relevant concentrations of the fungicide for a period of 96 h. Fludioxonil at 50–200 μg L−1 significantly limited the growth of both microalgae, especially in the first 24 h of the exposure, where inhibitions up to 82.34% were calculated. The toxicity of fludioxonil was further evaluated via the Microtox test, and the studied fungicide was found to be less toxic for the bacteria Aliivibrio fischeri. Regarding human cells, the fludioxonil’s toxic and cyto-genotoxic effects were assessed using the Trypan blue exclusion test and the Cytokinesis Block MicroNucleus (CBMN) assay. Cell viability in all fludioxonil-treated concentrations was similar to control values according to the results of the Trypan blue exclusion test. However, the CBMN assay was used and revealed that fludioxonil had genotoxic potential in higher concentrations and exerted cytotoxic activity against human lymphocytes. Specifically, only the highest dose of fludioxonil, i.e., 10 μg mL−1, exerted genotoxic effects against human lymphocytes, whereas treatment with 0.5, 1, and 5 μg mL−1 did not lead to statistically significant induction of micronuclei (MN) frequencies compared with the control culture. However, fludioxonil-mediated cytotoxicity was statistically significant, which was demonstrated by the decreased CBPI (cytokinesis block proliferation index) values in all cases except for the lowest dose, i.e., 0.5 μg mL−1.